Legalizing premium secondhand trade: Economic potential for Bali’s tourism special economic zones - Akhmad Firdiansyah; Putu Tegar Pradiawan (Educoretax, 2026)
This study analyzes the economic potential of legalizing the premium secondhand trade in Bali Province driven by tourist expenditures, utilizing the 2016 Tourism Satellite Account (TSA) framework and Input-Output (I-O) Table. A simulated shock of IDR 1.27 trillion was applied to the "Wholesale and Retail Trade; Repair of Motor Vehicles and Motorcycles" sector to measure the multiplier effects on output, wages, and employment within the tourism economy. The results demonstrate that the legalization of premium circular goods trade could generate a total output impact of IDR 1.65 trillion, an additional wage impact of IDR 72.20 billion, and create 25.23 thousand new jobs. These findings indicate that legalization through the Special Economic Zone (SEZ) mechanism holds substantial potential to transition previously prohibited economic activities into supportive components of a legal and sustainable tourism sector, enhance labor absorption, and strengthen Bali's green economy ecosystem. This study contributes to the broader discourse on transitioning from prohibited goods to restricted legality by demonstrating measurable economic benefits through TSA and I-O modeling. Policy implications suggest that a structured trade legalization approach via SEZ customs facilities—pursuant to Government Regulation (PP) No. 40/2021 and Minister of Finance Regulation (PMK) No. 33/PMK.010/2021—can serve as a strategic alternative to legalize the premium secondhand business, thereby optimizing sustainable economic potential in Bali and Indonesia.